Urgensi Nasionalisasi Penanaman Modal Asing oleh Pemerintah Republik Indonesia - Serlika Aprita; Hasanal Mulkan (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine the urgency of the nationalization of foreign investment by the Government of the Republic of Indonesia. The legal research method used is normative legal research. The Government of the Republic of Indonesia is currently in a position to nationalize foreign capital companies by prioritizing the potential of the nation and state and not closing themselves on the entry of foreign capital for the sake of realizing economic growth. Foreign investment in the perspective of Law Number 25 of 2007 concerning Investment must prioritize the welfare of the Indonesian people by prioritizing the potential possessed by the nation and state without neglecting Indonesia's economic and political sovereignty. the nationalization carried out by Bolivia, Venezuela and Mexico can be used as a comparison and lesson for the Government of the Republic of Indonesia in nationalizing that the President, he uses his power to realize the will of the people in the aim of restoring economic and political sovereignty over its natural resources.